Ekstrakurikuler Karawitan Di SDN Palur 02 - Anazitun, Laili Nur, Muhroji, SE, M.Pd. Msi (2017)
This study aimed to describe the karawitan extracurricular at SDN Palur 02. This research was conducted at SDN Palur 02 from October 2016 to February 2017. This study used a qualitative approach with descriptive qualitative research design. The technique data collection using are interviews,observation, and documentation. The data validity by triangulation of sources. The data analysis included data reduction, data presentation, and conclusion. The results of the studyare as follows : 1) Background of extracurricular musical at SDN Palur 02 is to introduce local culture (musicians) who endangered its existence amid the younger generation due to the influence of globalization, 2) Interest extracurricular musical SDN Palur 02 is to instill a love of culture to the students, to develop the potential and talent of the students in the arts, as well as to establish the character of students, 3) Planning karawitan extracurricular activities through meeting and was included in the musical RKS while learning plan have not been made in the form of written document RPP, 4) Organizing extracurricular musical SDN Palur 02 not have a committee or special teams. Organizing done by training teachers assisted by teachers and under the supervision of the school principal, 5) Implementation of karawitan extracurricular activities has been running smoothly. The implementation ot karawitan extracurricular activities include open activities, core activities, and last activities, 6) Evaluations have been done but has not made a written assessment format for the result of the karawitan extracurricular learning, 7) Supporting factors this activity is the motivation and enthusiasm of the students, all elements of the school and parents. Limiting factors of this activity is to time constraints, infrastructure is inadequate and financing during the race, 8) Efforts is to add an hour of exercise and provide adequate infrastructure.